Postcards from Venice: Life and the City in Paul Morand's Venises - Kimberly Philpot van Noort (Studies in 20th & 21st Century Literature, 2001)
Paul Morand's 1971 book Venises leads the reader on a labyrinthine path not only through the various manifestations of the city of Venice and of the life of the author that it presents, but also through the slippery experience of referentiality as the text engulfs the reader in proper names. This article traces Morand's simultaneous construction and destruction of the notion of a referential self as he pieces together his life in and around the city of Venice. By exploiting the complementary genres of autobiography and travel writing, Morand creates a dialogue between the city and the self, an exchange facilitated by the hydra-like city of Venice. Morand, like Proust, "does not say Venice by chance" as he capitalizes on the ever-receding signifier of Venice in order to provide a space in which to elide that particular self, Morand the collaborator, that he wishes to disappear amid the pluralities of his city of Venice. This pluralistic relationship of the self and the city and its consequent "disappearing act" consciously implicates both the position and the experience of the reader not only of Venises but of referential texts in general.
Keywords: Paul Morand; Venises; Venice; referential self; autobiography; travel writing; self; city; referential texts